Lipid-lowering therapy in high cardiovascular risk patients during COVID-19 pandemic: keep focused on the target - Cesaro, Arturo; Riccio, Carmine; Calabrò, Paolo (Monaldi Archives for Chest Disease, 2021)
To the Editor COVID-19 (COrona VIrus Disease) patients with cardiovascular (CV) disease, multiple CV risk factors or comorbidities (i.e., arterial hypertension and diabetes) were shown to be more prone to a worse prognosis. SARS-CoV-2 is a still unknown enemy and the role of concomitant cardiovascular therapies has been controversial in the early stages, particularly with regard to Angiotensin-Converting Enzyme inhibitors...